Agency and Transaction Cost Perspectives on the Manager-Shareholder Relationship: Incentives for Congruent Interests - Oviatt, Benjamin M. (Academy of Management Review, 1988)
This paper examines the manager-shareholder relationship through agency and transaction cost theories. The literature of those theories suggests several incentives and monitoring methods that may control opportunistic behavior among managers. Ten hypotheses are proposed concerning those incentives and monitoring methods, and methodological suggestions are made to motivate research regarding the congruence of managerial and shareholder interests.